Implementasi Program Keluarga Harapan (PKH) Terhadap Keluarga Sangat Miskin (KSM) Penerima Bantuan (Studi di Kecamatan Rindi Kabupaten Sumba Timur) - Pekuwali, Pelipus; Indartuti, Endang; Murti, Indah (Universitas 17 Agustus 1945 Surabaya, 2018)
This study aims to describe the implementation of Family Hope Program (PKH) in Rindi District, East Sumba Regency. This research uses qualitative descriptive method type. Data collection techniques used in the form of interviews to get a deep data from the sources. And Techniques The collection of data from existing sources is through records, archives, and documents, textbooks, existing both in the institution related to PKH and the libraries that deal with the research problems discussed. Informant research that includes the implementers, target groups and public figures in general. The results of this study show that PKH Implementation in Rindi Sub-district of East Sumba Regency has many obstacles and has not been implemented well, socialization and information distribution about PKH has not been fully known by the figures and society in general except the executing party and the target group, , And there is no clear SOP on PKH in Rindi District.Keywords: Implementation, Family Hope Program (PKH)